2020
DOI: 10.31234/osf.io/edhr5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathways from Socioeconomic Status to Early Academic Achievement: The Role of Specific Executive Functions

Abstract: Among the many factors contributing to the SES-achievement gap, executive function (EF) skills have received a considerable amount of attention, given their role in supporting academic skill development. While recent work has demonstrated that global EF constructs mediate SES-achievement relations, less attention has been paid to unpacking the role of specific EF components in linking SES to achievement. Data from the NICHD Study of Early Child Care and Youth Development (N = 1,273) were analyzed to assess dir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…For example, Kim et al (2020) found that EF explained the negative association for only two of the seven individual risk factors-age-for-grade and perceived community safety-on children's literacy and numeracy skills. Further, similar to the direct effects between EF and math, studies drawing on samples of children from high-income countries have found a stronger mediating relation between risk, EF, and math than for literacy or language abilities (Lawson & Farah, 2017;Nesbitt et al, 2013;Waters et al, 2020). In line with this evidence, we found that EF explained a larger proportion of the relation between cumulative risk and math than for literacy (100.0% vs. 65.3%, respectively) in our sample.…”
Section: Mediation Effectssupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Kim et al (2020) found that EF explained the negative association for only two of the seven individual risk factors-age-for-grade and perceived community safety-on children's literacy and numeracy skills. Further, similar to the direct effects between EF and math, studies drawing on samples of children from high-income countries have found a stronger mediating relation between risk, EF, and math than for literacy or language abilities (Lawson & Farah, 2017;Nesbitt et al, 2013;Waters et al, 2020). In line with this evidence, we found that EF explained a larger proportion of the relation between cumulative risk and math than for literacy (100.0% vs. 65.3%, respectively) in our sample.…”
Section: Mediation Effectssupporting
confidence: 89%
“…A small body of research from the United States has shown that EF partially explains the negative associations between adversity and children’s academic outcomes in early and middle childhood (Lawson & Farah, 2017; Waters et al, 2020). Extending this line of work generally—and to SSA and other LMICs in particular—is a fruitful area of investigation.…”
Section: Executive Function and Learning Outcomesmentioning
confidence: 99%
“…Given that EF is associated with both SES and academic achievement, EF has been proposed to mediate SES and academic achievement, including literacy. Indeed, several studies have implicated EF in SES-related gaps in academic achievement, including both school readiness (Dilworth-Bart, 2012;Fitzpatrick et al, 2014;Micalizzi et al, 2019) and school achievement across childhood and adolescence (Lawson & Farah, 2017;Nesbitt et al, 2013;Sektnan et al, 2010;Waters et al, 2021) the primary school net enrollment rate is 91.1%, only 73.26% of children will complete primary school (UNESCO, 2016; UNESCO Institute for Statistics, 2014). The age at which a child begins their schooling is highly variable.…”
Section: Ses and Literacy In Lmicsmentioning
confidence: 99%
“…Two of the cognitive domains most strongly associated with SES are language skills (for review, see Pace et al., 2017) and executive functioning (EF) skills (for review, see Lawson et al., 2018). Both sets of skills are critical for academic learning, and differences in language and EF each contribute to SES‐related disparities in academic achievement (e.g., Burchinal et al., 2002; Durham et al., 2007; Fitzpatrick et al., 2014; Lawson & Farah, 2017; Rosen et al., 2018; Waters et al., 2021).…”
Section: Introductionmentioning
confidence: 99%